2006
DOI: 10.1302/0301-620x.88b12.17309
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical and radiological outcome in patients with fractures of the acetabulum and concomitant posterior dislocation of the hip

Abstract: We aimed to identify variables associated with clinical and radiological outcome following fractures of the acetabulum associated with posterior dislocation of the hip. Using a prospective database of 1076 such fractures, we identified 109 patients with this combined injury managed operatively within three weeks and followed up for two or more years. The patients had a mean age of 42 years (15 to 79), 78 (72%) were male, and 84 (77%) had been involved in motor vehicle accidents. Using multivariate analysis the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 22 publications
(36 reference statements)
5
70
1
3
Order By: Relevance
“…3,4,6,7,30,31,38 It has been shown that the quality of reduction assessed in the immediate post-operative period determines the development of osteoarthritis requiring total hip replacement. 1,2,24 In this case series, the post-operative residual displacement was < 3 mm in 28 of the 30 cases (93.3%), and at the time of final radiological assessment 9 20 of 26 (76.9%) maintained their good to excellent outcome. Two cases had an unsatisfactory reduction and a poor final radiological score, but reported good to fair function.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…3,4,6,7,30,31,38 It has been shown that the quality of reduction assessed in the immediate post-operative period determines the development of osteoarthritis requiring total hip replacement. 1,2,24 In this case series, the post-operative residual displacement was < 3 mm in 28 of the 30 cases (93.3%), and at the time of final radiological assessment 9 20 of 26 (76.9%) maintained their good to excellent outcome. Two cases had an unsatisfactory reduction and a poor final radiological score, but reported good to fair function.…”
Section: Discussionmentioning
confidence: 56%
“…1,12,20,21 There is ample evidence that surgery for displaced acetabular fractures results in a favourable outcome. [21][22][23][24] To our knowledge, only the Letournel series 1 has so far provided substantial evidence on the outcome of individual simple acetabular fracture patterns such as anterior column and or anterior wall fractures. This can be attributed to their rarity and the fragmentation of experience between different trauma centres.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Asetabulum kırıklarının büyük çoğunluğu yük taşıyan tavanı ilgilendirir. Bu bölgedeki en küçük düzensizlik eklemdeki artroza gidiş sürecini hızlandırır.…”
Section: Kırık İle İlgi̇li̇ Faktörlerunclassified
“…Göreceli sık görülmelerine ve ortopedistlerin büyük bölümü tarafından cerrahi olarak tedavi edilmelerine rağmen büyük serilerde en kötü sonuç-lar yine göreceli olarak sık karşılaşılan bu kırıkla-ra bağlıdır. [9,10,12,17] Genel olarak BT incelemelerinde posteriyor duvar bütünlüğünün %50'sinden azının korunmuş olması kararsızlık işareti olarak kabul gör-müştür ve cerrahi endikasyonudur. [18] Ancak duvar bütünlüğünün %80'inin korunduğu posteriyor duvar kırıklarında da kararsızlık nedeniyle cerrahi uygulanabilir.…”
Section: Kırık Tipiunclassified
“…paction of the posterior wall, [8,9] hip dislocation related to the posterior wall, [9,10] and femoral head injuries have been noted as poor results after internal fixation. [2,11] These complications increase the risk of neurovascular traumatization, loss of height, and aseptic and septic loosening.…”
mentioning
confidence: 99%